Analysis of risk factors related to the incidence of site infections in gastrosurgeries - Poveda, Vanessa de Brito; Galvão, Cristina Maria; Hayashida, Miyeko (Revista da Escola de Enfermagem da USP, 2003)
Nosocomial infection is regarded as a serious problem whose incidence and complexity has been increasing, thus generating various types of social and economic implications. This investigation aimed at assessing the incidence of surgical site infection and risk factors in patients submitted to elective surgeries in the specialty of gastroenterology performed in a public hospital in the interior of São Paulo State. Data were collected by means of a retrospective study of medical records from January to December 1999. Of the 134 cases under study, the occurrence of surgery site infection was detected in 18 situations (13.4%). Nine cases (50%) were considered to be superficial incisional infections, 8 (44.4%) were deep incisional infections and 1 (5.5%) was an organ/space infection. With respect to the risk factors, the ones with percentage higher or equal to 50% were: age above 50 years, the presence of neoplasia, surgeries that last more than two hours and inadequate trichotomy.